Konsep Mudharabah Dalam Mendukung Umkm di Masa Pandemi Covid-19 - Fawahan, Lian; Marianingsih, Ita (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to analyze the concept of mudharabah financing in supporting MSMEs during the covid-19 pandemic. This study uses qualitative descriptive that uses literature studies quoted from book journals and relevant websites. The purpose of this study is to provide alternatives for MSMEs in the face of the covid-19 pandemic and help the Indonesian economy as a whole. The result of the study show that mudharabah financing with a revenue sharing system can relieve MSMEs during the Covid-19 pandemic. With the financing of mudharabah MSME actors get capital in the time of the pandemic crisis without being burdened with interest because the concept of Mudharabah is not only about profit sharing but also about for loss, where MSME actors as mudharib and Islamic banks as shohibul maal. Islamic banks with the concept of Mudharabah Muqayyaddah also give directions to MSME actors about businesses that have opportunities in the Covid-19 pandemic. So Islamic bank not only provide capital but also provide education to MSME actors.